2019
DOI: 10.3389/fpsyg.2019.00102
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Models for Response Times and Processes in Cognitive Tests

Abstract: Response times (RTs) are a natural kind of data to investigate cognitive processes underlying cognitive test performance. We give an overview of modeling approaches and of findings obtained with these approaches. Four types of models are discussed: response time models (RT as the sole dependent variable), joint models (RT together with other variables as dependent variable), local dependency models (with remaining dependencies between RT and accuracy), and response time as covariate models (RT as independent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
169
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(177 citation statements)
references
References 88 publications
7
169
0
1
Order By: Relevance
“…This suggests that although the variation of time effects is small relative to the ability variation, these models change the interpretation of ability itself, as other research has shown [De Boeck, & Jeon, 2019;Bolsinova, et. al, 2017].…”
Section: Conclusion and Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This suggests that although the variation of time effects is small relative to the ability variation, these models change the interpretation of ability itself, as other research has shown [De Boeck, & Jeon, 2019;Bolsinova, et. al, 2017].…”
Section: Conclusion and Discussionmentioning
confidence: 87%
“…However, to process such data, it is necessary to have a fitting statistical model which utilizes this information [De Boeck, & Jeon, 2019]. This means that items become described by more and more parameters, which more precisely describe the probability of a correct response in terms of information processing.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we begin with discussions of statistical and psychological approaches for understanding interplay between speed and accuracy. Other accounts aim to be relatively comprehensive [7,8], we focus on specific features of both approaches that are relevant given our data and findings.…”
Section: Interplay Of Speed and Accuracymentioning
confidence: 99%
“…Figure 5 (Panel B) contains results from stratified models wherein log(t) is first residualized based on a simple version of Eqn 5 including only sequence number and item/person fixed effects. 7 Note that these residuals are similar to the z pi in [26]. We then use the residuals, denoted ∆ pi , to predict accuracy in a simplified version of Eqn 6.…”
Section: Ability-based Heterogeneity In Response Accelerationmentioning
confidence: 99%